Use of a maternal newborn audit and feedback system in Ontario: a collective case study. Issue 8 (16th February 2019) - Reszel, Jessica; Dunn, Sandra I; Sprague, Ann E; Graham, Ian D; Grimshaw, Jeremy M; Peterson, Wendy E; Ockenden, Holly; Wilding, Jodi; Quosdorf, Ashley; Darling, Elizabeth K; Fell, Deshayne B; Harrold, JoAnn; et al.
Abstract : Background: As part of a larger study examining the effectiveness of the Maternal Newborn Dashboard, an electronic audit and feedback system to improve maternal-newborn care practices and outcomes, the purpose of this study was to increase our understanding of factors explaining variability in performance after implementation of the Dashboard in Ontario, Canada. Methods: A collective case study. A maximum variation sampling approach was used to invite hospitals reflecting different criteria to participate in a 1-day to 2-day site visit by the research team. The visits included: (1) semistructured interviews and focus groups with healthcare providers, leaders and personnel involved in clinical change processes; (2) observations and document review. Interviews and focus groups were audio-recorded and transcribed verbatim. Qualitative content analysis was used to code and categorise the data. Results: Between June and November 2016, we visited 14 maternal-newborn hospitals. Hospitals were grouped into four quadrants based on their key indicator performance and level of engagement with the Dashboard. Findings revealed four overarching themes that contribute to the varying success of sites in achieving practice change on the Dashboard key performance indicators, namely, interdisciplinary collaboration and accountability, application of formal change strategies, team trust and use of evidence and data, as well as alignment with organisational priorities and support. Conclusion: The diversity of facilitators and barriers across the 14 hospitals highlights the need to go beyond a 'one size fits all' approach when implementing audit and feedback systems. Future work to identify tools to assess barriers to practice change and to evaluate the effects of cointerventions to optimise audit and feedback systems for clinical practice change is needed.